THE INDO-PACIFIC PIVOT: INDIA–CHINA RIVALRY AND ITS GEOPOLITICAL IMPLICATIONS - Kumar, Sudhanshu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Indo-Pacific has quickly become the geostrategically most disputed region of modern geopolitics, a portrayal of increasing India–China rivalry. This competition is no longer just limited to the land frontiers but has extended to sea spaces, trade routes, multilateral forums, and regional states' influence. China's far-reaching Belt and Road Initiative (BRI), growing naval presence, and port infrastructure initiatives across the Indian Ocean and Pacific Rim reveal a calculated approach to gaining long-term geopolitical benefits. At the same time, India has readjusted its strategic position through efforts such as the Act East Policy, Indo-Pacific Oceans Initiative, and proactive engagement with forums like the Quad (Quadrilateral Security Dialogue). These steps represent India's shift toward a more proactive regional role, seeking to balance China's rising influence. This analysis examines the transforming India–China rivalry in the Indo-Pacific, evaluating its causes, expressions, and wider geopolitical connotations. It concentrates on three essential aspects: strategic-military rivalry, economic influence and connectivity, and the shifting regional alliances. Whereas China is pursuing dominance in terms of economic reliance and access to sea chokepoints, India is pursuing counter-balancing efforts through security alliances, regional diplomacy investment, and naval modernization. The rivalry is compounded by reactions from smaller Indo-Pacific nations, most of which follow a hedging policy—collaborating with both powers while remaining independent. The interference of extra-regional powers like the United States, Japan, and Australia contributes other layers to the regional powers. The study follows a mixed-methods methodology, bringing together strategic analysis, empirical evidence, and regional case studies to map the trajectory of rivalry and its influence on regional stability, freedom of navigation, and security architectures. In order to predict future hotspots, assess strategic choices for regional actors, and isolate opportunities for diplomatic initiative, the Indo-Pacific pivot must be understood in the context of India–China competition. Through a rigorous examination of the major drivers, trends, and likely outcomes of this competition, the study adds to the subtle appreciation of the ways in which the Indo-Pacific world is being remade by two of Asia's leading powers. Finally, the conclusions will guide policy advice that can help to promote a stable, inclusive, and rules-based regional order.